UTILIZING GADGETS AND ONLINE GAMES AS MEANS OF SELF-DEVELOPMENT OF STUDENTS / I SMP NEGERI 3 BILAH HULU IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Riadi, Slamat; Prayoga, Yudi; Halim, Abd (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Revolution is change that happens quickly. The revolution had a huge impact on society. Society quickly accepted the effects of the new revolution. The revolution has undergone four changes during its development. Online games themselves have positive and negative impacts. The effect of the meaning of obtaining positive benefits from online games, namely: being able to develop one's visuospatial abilities by practicing processing spatial information from the monitor screen. Therefore, the right way to overcome this problem is through community service in the form of outreach. The purpose of this study is to find out how the use of gadget technology and online games in learning in the era of the industrial revolution 4.0. This research is qualitative descriptive research. The research was conducted on students of SMP Negeri 3 Bilah Hulu, Labuhanbatu Regency.